2013
DOI: 10.1051/epjconf/20134501079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particle deposition in a lung model using an individual path

Abstract: Abstract. Suspended particles can cause a wide range of chronic respiratory illnesses such as asthma and chronic obstructive pulmonary diseases, as well as worsening heart conditions and other conditions. To know the particle depositions in realistic models of the human respiratory system is fundamental to prevent these diseases. The main objective of this work is to study the lung deposition of inhaled particles through a numerical model using UDF (User Defined Function) to impose the boundary conditions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
7
0
8
Order By: Relevance
“…Currently, in silico studies addressed to respiratory lung modeling have been covering detailed patient-specific 3D lung reconstruction [13,14], nasopharynx-trachea ventilation features [6,7,15], 3D-1D coupling of upper and middle airway segments, and FSI simulations [16]. The lumped models operate with lung mechanics in terms of tidal volume and pressure with lower details [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in silico studies addressed to respiratory lung modeling have been covering detailed patient-specific 3D lung reconstruction [13,14], nasopharynx-trachea ventilation features [6,7,15], 3D-1D coupling of upper and middle airway segments, and FSI simulations [16]. The lumped models operate with lung mechanics in terms of tidal volume and pressure with lower details [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…where V n p is an element of discrete function which is defined on the mesh and represents mesh analog for the V from Equation (15). This mesh is uniform along the x axis:…”
Section: Numerical Implementationmentioning
confidence: 99%
“…The resultant graph of the bronchial tree contains up to seven generations. Two torus configurations were used to design an individual bifurcation in [7][8][9] (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the reduced geometry approach has been coupled with realistic, CT-scan-based computational geometries to provide realistic yet efficient CFD models for steady-state inhalation [17]. Recent studies have adopted the most limiting case of a reduced-geometry approach, in which a single flow path is modeled as a representative example of the flow through all investigated generations of airflow [18][19][20][21]. Figure 1 provides an illustration of the reduced-geometry approach, based on truncation of selected airway branches.…”
Section: Introductionmentioning
confidence: 99%
“…Among studies employing reduced-geometry models, five different approaches can be identified for specification of boundary conditions at truncated airway boundaries. These may be summarized as: specified pressure [23], specified mass flow rate [18][19][20][21]24], impedance modeling [25,26], 1D modeling of truncated branches [11,13], and stochastic coupling of interior and outlet zones [12,16,17]. The first two approaches are selfexplanatory.…”
Section: Introductionmentioning
confidence: 99%